Hubungan Asupan Protein Dan Status Gizi Dengan Kadar Hemoglobin Ibu Hamil Di Desa Demakan Kecamatan Mojolaban Kabupaten Sukoharjo - PRATIWI, IKA YULIA, Dyah Intan Puspitasari, S. Gz., M.Nutr (2017)
Introduction: Anemia is a condition where the body has a low level of red blood cell (erythocytes) containing hemoglobin, which have a role to circulate oxygen throughout the body. Anemia in pregnant women are known to have a negative impact on the health both for the mother and the baby. Factors that affect the hemoglobin level on pregant women: the lack of iron and protein intake, and an increase of iron and multivitamin requirement. Objective: To determine the association of protein intake and nutritonal status to hemoglobin level of pregant women in Demakan, Mojolaban, Sukoharjo. Method: This is observational research with crosssectional design. A total of 34 pregnant woman were recruited using simple random sampling. The data on protein intake were obtained by 24 hours unconsecutive food recall. Nutritional status data were obtained by measuring MUAC (Mid-Upper Arm Circumference) which then compared to the standart. Data on hemoglobin level was obtained using cyanmethemoglobin method. The data were analyzed using a Pearson Product Moment. Results: The results show that there is no association between nutritional status and hemoglobin level (p = 0.687). There is an association between protein intake and hemoglobin level (p value=0.043). Conclusion: There is no association between nutritional status with hemoglobin level. There is an association between protein intake and hemoglobin level.